KEKUATAN MENGIKAT PERJANJIAN SECARA LISAN - Juliati Br Ginting (The Juris, 2022)
Agreements are activities that are very commonly carried out by the community to carry out activities related to buying and selling, lending and borrowing, work agreements and other business ventures. Agreements can be made orally and can be made in writing. Oral agreements are usually carried out in indigenous peoples for simple legal ties, while written agreements are usually carried out by relatively modern people who are related to businesses whose legal relations are more complex. The problems to be discussed in this study are the binding strength of an agreement made orally. Therefore this paper also aims to determine the extent to which the binding force of the verbal agreement made by the parties. The method used in this research is the normative method, namely focusing research on legal principles and reviewing and examining written regulations. In terms of knowing the binding power of an agreement made orally. So an oral agreement is an agreement that must be carried out by the parties, because in the verbal agreement the elements of an agreement have been fulfilled. With a strong and clear legal basis, it is hoped that the parties will carry out their rights and obligations according to what has been agreed upon, so that no party feels disadvantaged.